KOLABORASI ORGANISASI DALAM MENGIMPLEMENTASIKAN PROGRAM KELUARGA HARAPAN (PKH) DI DESA SISARAHILIGAMO KECAMATAN GUNUNGSTOLI KOTA GUNUNGSITOLI - Telaumbanua, Lestariani; Ndraha, Ayler Beniah; Mendrofa, Yupiter; Waruwu, Sukaaro (FEB Universitas Sam Ratulangi Manado, 2023)
This thesis research aims to find out how Organizational Collaboration in implementing the Family Hope Program (PKH) in Sisarahiligamo Village, Gunungstoli Subdistrict, Gunungsitoli City, then also researchers want to know what are the supporting and inhibiting factors of organizational collaboration in implementing PKH in Sisarahiligamo Village. The organizations that are the focus of this research are the Sisarahiligamo village government, the Gunungsitoli sub-district government and the Gunungsitoli City Social Service. This type of research is descriptive with a qualitative approach, using data collection techniques with interviews, observation and documentation studies. This research uses the Collaborative Governance theory proposed by Ansell and Gash to analyze organizational collaboration in the implementation of PKH in Sisarahiligamo Village. The results of this study show that the administrative rules of collaboration have been carried out well starting from the face-to-face dialog that has been carried out, the establishment of a relationship of mutual trust, the existence of mutual commitment, the existence of mutual understanding, and the impact of the results of the collaboration carried out. The sustainability of collaboration is supported by the existence of strong rules regarding the implementation of PKH and the existence of competent human resources in PKH assistance in the field. In the process, there are still several factors that make the collaboration carried out by the Social Service, the Gunungsitoli sub-district government and the Sisarahiligamo village government not optimal, such as frequent changes in the PKH social assistance mechanism and also the lack of budget provided by the City government in the implementation of PKH in Gunungsitoli City, especially in supporting the acceleration of poverty data improvement which is the PKH Program database.